Novel antiangiogenic therapy targeting biglycan using tumor endothelial cell‐specific liposomal siRNA delivery system. Issue 5 (21st March 2022) - Maishi, Nako; Sakurai, Yu; Hatakeyama, Hiroto; Umeyama, Yui; Nakamura, Takashi; Endo, Rikito; Alam, Mohammad Towfik; Li, Cong; Annan, Dorcas Akuba‐Muhyia; Kikuchi, Hiroshi; Morimoto, Hirofumi; Morimoto, Masahiro; et al.
Abstract: Tumor blood vessels play important roles in tumor progression and metastasis. Targeting tumor endothelial cells (TECs) is one of the strategies for cancer therapy. We previously reported that biglycan, a small leucine‐rich proteoglycan, is highly expressed in TECs. TECs utilize biglycan in an autocrine manner for migration and angiogenesis. Furthermore, TEC‐derived biglycan stimulates tumor cell migration in a paracrine manner leading to tumor cell intravasation and metastasis. In this study, we explored the therapeutic effect of biglycan inhibition in the TECs of renal cell carcinoma using an in vivo siRNA delivery system known as a multifunctional envelope‐type nanodevice (MEND), which contains a unique pH‐sensitive cationic lipid. To specifically deliver MEND into TECs, we incorporated cyclo(Arg–Gly–Asp–D –Phe–Lys) (cRGD) into MEND because αV β3 integrin, a receptor for cRGD, is selective and highly expressed in TECs. We developed RGD‐MEND‐encapsulating siRNA against biglycan. First, we confirmed that MEND was delivered into OS‐RC‐2 tumor‐derived TECs and induced in vitro RNAi‐mediated gene silencing. MEND was then injected intravenously into OS‐RC‐2 tumor‐bearing mice. Flow cytometry analysis demonstrated that MEND was specifically delivered into TECs. Quantitative RT‐PCR indicated that biglycan was knocked down by biglycan siRNA‐containing MEND. Finally, we analyzed the therapeutic effect of biglycan silencing by MEND in TECs. Tumor growth was inhibited by biglycan siRNA‐containing MEND. Tumor microenvironmental factors such as fibrosis were also normalized using biglycan inhibition in TECs. Biglycan in TECs can be a novel target for cancer treatment. Abstract : Targeting tumor endothelial cells (TECs) is one of the strategies for cancer therapy. In this study, we targeted biglycan in TECs using an in vivo siRNA delivery system known as a multifunctional envelope‐type nanodevice (MEND). We report, for the first time, that TEC‐specific marker inhibition using an in vivo siRNA delivery system can cause therapeutic effects in tumors.